Photoluminescence Characteristics of Yag:Ce, Gd Based Phosphors with Different Prehistories; Russian Physics Journal; Vol. 60, iss. 5 - Lisitsyn V. M. Viktor Mikhailovich; Soshchin N. P. Naum Petrovich; Yangyang Yu.; Stepanov S. A. Sergey Aleksandrovich; Lisitsyna L. A. Lyudmila Aleksandrovna; Tulegenova A. T. Aida Tulegenkyzy; Abdullin Kh. A. Khabibulla Abdullaevich (2017, 2017)
Title screen